TEOLOGI MU’TAZILAH: Sebuah Upaya Revitalisasi - Safii Safii (Jurnal Theologia, 2014)
This article elaborates an important role in the history of Mu'tazila theology in the Islamic World. Services that have been provided by this school seems to be forgotten by the Muslims, even it became despised and persecuted theology. In fact, this theology has made a large contribution in defending against attacks originating from the Jews, Christians, Zoroastrians, and Materialist. In the modern context, the spirit of this theology is relevant to be recalled that the freedom of thought as an integral part of the human being can grow and develop so that science and technology in the Islamic world can grow back. It must be recognized that this is indeed the flow had already given a negative image by traditional Islamic theology and hadith experts. Theology is imaged as a carrier of heresy